PENGARUH KUALITAS FUNGSIONAL DAN CITRA PERUSAHAAN TERHADAP WORD OF MOUTH COMMUNICATION DIMEDIASI KEPUASAN KONSUMEN PADA KONSUMEN SENORITA BAKESHOP - Kholifah Kholifah (LP3M Universitas Putra Bangsa, 2022)
The purpose of this study was to analyze the effect of functional quality and corporate image on word of mouth communication mediated by consumer satisfaction on consumers of Senorita Bakeshop. Respondents in this study were consumers of Senorita Bakeshop, totaling 100 respondents. The sampling technique used was purposive sampling. The method in this study uses path analysis. The results of this study indicate that Functional Quality affects consumer satisfaction, corporate image affects consumer satisfaction, Functional Quality affects word of mouth communication, corporate image affects word of mouth communication, consumer satisfaction affects word of mouth communication, there is an effect of functional quality on word of mouth communication through customer satisfaction, there is no influence of corporate image on word of mouth communication through customer satisfaction.